Working the crowd: sociable vervets benefit by reducing exposure to risk. (28th January 2016) - Josephs, Nathan; Bonnell, Tyler; Dostie, Marcus; Barrett, Louise; Henzi, S. Peter
Lay Summary: Social animals can find safety from predators by staying close to others but may experience increased competition for resources in doing so. We therefore expect to find dominant animals at the center of groups and lower-ranking ones at the margins. Accurate positional data from members of 2 large vervet monkey troops, however, show that more sociable—but not more dominant—animals both avoid predation risk and forage more efficiently while do so. Abstract: Reduction of predation risk represents the most likely explanation for the evolution of group-living among the anthropoid primates. Obligate sociality leads to increased competition for resources, meaning that animals may face a trade-off between safe positions within the troop and increased foraging efficiency. Dominance has been proposed to be a major factor influencing spatial position within primate troops, but it is also possible that animals can improve their spatial position using social strategies, such as grooming. In many species, dominance rank and social preference (as expressed through grooming) are confounded. In our study population of vervet monkeys, however, dominance does not underpin social preference, enabling us to test whether 1) more sociable vervets experience reduced exposure to predation risk, as indexed by vigilance, and 2) that dominant animals accepted increased risk in order to forage at the front of the troop. We collected spatially explicit data on the individual locations of members of 2 troops at predetermined times over a 4-month period. We constructed bounded Voronoi tessellations for each temporal snapshot, with the area of each animal's "tile" identifying its "domain of danger." We also collected data on time spent vigilant and foraging, dominance rank, and grooming behavior. We found no effect of dominance, but animals with larger grooming networks were less exposed to predation risk, from which they benefitted through both reduced vigilance and increased foraging time. We interpret these results in the light of current debates about the ways in which sociality affects fitness.